2009
DOI: 10.1177/0193723509350611
|View full text |Cite
|
Sign up to set email alerts
|

Something Less than a Driver: Toward an Understanding of Gendered Bodies in Motorsport

Abstract: This essay argues that the gendered body is not accounted for in the physical conditions of motorsport but instead through the discourse of the sport. Specifically, women’s bodies signify as different in three main ways: beyond vehicles (navigating the space filled with other bodies and their respective vehicles), with vehicles (coordinating with the technology of the vehicle), and inside vehicles (operating in the space of and interacting with the technology) but situated by their gender’s discursively constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Most sports involve degradation of the environment, but rarely as an overt component of their very essence. Yet, along with its hypermasculine First World class base and industrial showmanship, Formula 1 motor racing combines all these factors (Pflugfelder, 2009). It is an unusual business-and a very big one.…”
Section: Formulamentioning
confidence: 99%
“…Most sports involve degradation of the environment, but rarely as an overt component of their very essence. Yet, along with its hypermasculine First World class base and industrial showmanship, Formula 1 motor racing combines all these factors (Pflugfelder, 2009). It is an unusual business-and a very big one.…”
Section: Formulamentioning
confidence: 99%
“…Some literature has concentrated on different aspects of motor sports or other leisure activities, but none is on the management of community-based information, which is of interest in this research. For example, Pflugfelder (2009) examined gender differences, such as women drivers in a male-dominated sport; and Ross, Ridinger and Cuneen (2009) discussed the success of women like Indy driver Danica Patrick who endorse products through their expertise and attractiveness. Dannefer (1980Dannefer ( , 1981 reported that historic car collectors are not 'mere car enthusiasts but passionate enthusiasts' whose interest dominates their leisure thoughts and activities (1981, p. 397).…”
Section: Camsmentioning
confidence: 99%
“…The purpose of past and present automaker strategies, argue Scharff, Cowan, and Walsh, was not only to construct women as a separate consumer base with different automotive needs and desires, but also to reinforce and maintain prescribed gender roles in home and on the road. Recent scholarship within multiple disciplines has made note of women's resistance to pervasive woman driver stereotypes through the assumption of new driver identities associated with the “chick” car (Lezotte, “Chick”), the classic muscle car (Lezotte, “Muscle”) and racing (Pflugfelder, Sloop). Attention to alternative woman driver positions demonstrates that, despite the efforts of automakers to shape women's driving habits and automotive choices, women continue to make informed and independent decisions on the cars they drive and how they use them.…”
Section: Car Songs Women's Voices and The “Woman Driver”mentioning
confidence: 99%